12
$\begingroup$

How do I find the value of this integral?

$$I=\int_{0}^{\Large\frac{\pi}{4}} \ln {(\sin x)}\cdot\ln {(\cos x)} \left(\dfrac{\ln{(\sin x)}}{\cot x}+\dfrac{\ln {(\cos x)}}{\tan x}\right)dx$$

I tried substituting $t=\ln {(\sin x)}\cdot \ln {(\cos x)}$ and $t=\dfrac{\ln {(\sin x)}}{\ln {(\cos x)}}$, but it isn't working.

$\endgroup$
  • $\begingroup$ Did you try to substitute $t=\sin x$? It may be a better option since $\frac{\ln(\sin x)}{\cot x} = \frac{\ln (\sin x)\sin x}{\cos x}$... $\endgroup$ – 5xum Jul 24 '14 at 10:39
  • $\begingroup$ No i didn't, but i will now. $\endgroup$ – pkwssis Jul 24 '14 at 10:39
  • $\begingroup$ You can use the techniques I used to solve this problem $\endgroup$ – Mhenni Benghorbal Jul 24 '14 at 10:40
  • 1
    $\begingroup$ When $\sin x$ and $\cos x$ show up in the integral, it is often useful to make the following substitution: $$\tan{x \over 2}=t$$ With this sub the terms will be $$\sin x = {2t\over 1+t^2}\\ \cos x={1-t^2 \over 1+t^2}\\ dx = {2dt \over 1+t^2}$$ Try to make this and play around (you also need to pay attention to the integration borders, as they change with making the substitution). $\endgroup$ – Dmitry Kazakov Jul 24 '14 at 10:43
  • $\begingroup$ @DmitryKazakov I can't get to anything useful using that substitution...it keeps getting longer.. how did you do it? $\endgroup$ – pkwssis Jul 24 '14 at 10:53
15
$\begingroup$

We will prove that $$I=-\frac{\pi^4}{2880}.$$ Indeed, let $$ J=\int_0^{\pi/2}\log^2(\sin x)\log(\cos x)\tan x \,dx $$ It is easy to see that $$\eqalign{J&=\int_0^{\pi/4}\log^2(\sin x)\log(\cos x)\tan x \,dx+ \int_{\pi/4}^{\pi/2}\log^2(\sin x)\log(\cos x)\tan x \,dx\cr &=\int_0^{\pi/4}\log^2(\sin x)\log(\cos x)\tan x \,dx+ \int_{0}^{\pi/4}\log^2(\cos x)\log(\sin x)\cot x \,dx\cr &=I }$$ Now, to calculate $J$ we make the substitution $t\leftarrow\sin^2x$: $$ J=\frac{1}{16}\int_0^1\frac{\log(1-u)}{1-u}\log^2(u)\,du $$ But $$\frac{\log(1-u)}{1-u}=-\left(\sum_{n=0}^\infty u^n\right)\left(\sum_{n=1}^\infty \frac{u^n}{n}\right) =-\sum_{n=1}^\infty H_nu^n $$ where $H_n=\sum_{k=1}^n1/k$. Hence $$J=-\frac{1}{16}\sum_{n=1}^\infty H_n\int_0^1u^n\log^2(u)du =-\frac{1}{8}\sum_{n=1}^\infty\frac{ H_n}{(n+1)^3} $$ Finally, since $H_{n}=H_{n+1}-\frac{1}{n+1}$, we get $$J=\frac{1}{8}\zeta(4)-\frac{1}{8}\sum_{n=1}^\infty\frac{H_n}{n^3}\tag{1}$$

The sum $\sum_{n=1}^\infty\frac{H_n}{n^3}$ is known, it can be evaluated as follows, first we have $$ H_n=\sum_{k=1}^\infty\left(\frac{1}{k}-\frac{1}{k+n}\right)= \sum_{k=1}^\infty \frac{n}{k(k+n)} $$ Thus $$ \sum_{n=1}^\infty\frac{H_n}{n^3}=\sum_{k,n\geq1}\frac{1}{n^2k(n+k)} =\sum_{k,n\geq1}\frac{1}{k^2n(n+k)} $$ Taking the half sum we find $$ \sum_{n=1}^\infty\frac{H_n}{n^3}=\frac{1}{2}\sum_{k,n\geq1}\frac{1}{kn(k+n)}\left(\frac{1}{k}+\frac{1}{n}\right)= \frac{1}{2}\sum_{k,n\geq1}\frac{1}{k^2n^2}=\frac{1}{2}\zeta^2(2) $$

Replacing in $(1)$ we obtain $$J=\frac{1}{8}\zeta(4)-\frac{1}{16}\zeta^2(2)=-\frac{\pi^4}{2880}.$$ as announced.$\qquad\square$

$\endgroup$
  • $\begingroup$ Wow..thanks Professor Kouba!! What a great answer! $\endgroup$ – pkwssis Jul 24 '14 at 11:38
  • $\begingroup$ Oh dear. Now I understand why Wolfram alpha couldn't find the solution. They should start scanning this site to improve their answers. $\endgroup$ – Matt B. Jul 24 '14 at 12:36
  • $\begingroup$ @Pkwssis: To evaluate $ \sum_{n=1}^\infty\frac{H_n}{n^3} $ you can use the integral representation which I introduced for Euler sums $B(p,q)$. Your case is $B(1,3)$. Then you need to evaluate the corresponding integral which is not hard. $\endgroup$ – Mhenni Benghorbal Jul 24 '14 at 14:31
  • $\begingroup$ I use the $\Gamma$ function to evaluate this integral. Comparing to your solution, it is a little long. $\endgroup$ – xpaul Aug 21 '14 at 19:47
  • $\begingroup$ There is a simple derivation of $\displaystyle{\large\sum_{n = 1}^{\infty}{H_{n} \over n^{3}} = {\pi^{4} \over 72}}$. $\endgroup$ – Felix Marin Aug 21 '14 at 19:56
3
$\begingroup$

Here I use the Beta function to evaluate this integral and the calculation is a little bit tedious. As Omran Kouba did, \begin{eqnarray} I&=&\int_{0}^{\Large\frac{\pi}{2}} \ln^2 {(\sin x)}\cdot\ln {(\cos x)}\tan xdx. \end{eqnarray} Let $$ J(a,b)=\int_0^{\frac{\pi}{2}}\sin^ax\cos^bx\tan xdx. $$ Then clearly $$ \frac{\partial^3 J(0,0)}{\partial a^2\partial b}=I.$$ Now, by the change of variables $\sin x\to t$ and then $t^2\to u$, it is easy to see \begin{eqnarray} J(a,b)=\frac{\Gamma(1+\frac{a}{2})\Gamma(\frac{b}{2})}{2\Gamma(1+\frac{a+b}{2})}. \end{eqnarray} Noting $\Gamma'(x)=\Gamma(x)\psi_0(x), \Gamma''(x)=\Gamma(x)\psi_0^2(x)+\Gamma(x)\psi_1(a)$, we have \begin{eqnarray} \frac{\partial^2 J(a,b)}{\partial a^2}&=&\frac{\Gamma(1+\frac{a}{2})\Gamma(\frac{b}{2})}{8\Gamma(1+\frac{a+b}{2})}[\psi_0^2(1+\frac{a}{2})-2\psi_0(1+\frac{a}{2})\psi_0(1+\frac{a+b}{2})\\ &&+\psi_0^2(1+\frac{a+b}{2})+\psi_1(1+\frac{a}{2})-\psi_1(1+\frac{a+b}{2})]. \end{eqnarray} Using $$ \Gamma(1)=1, \psi_0(1)=\gamma, \psi_1(1)=\frac{\pi^2}{6}, $$ we obtain $$ \frac{\partial^2 J(0,b)}{\partial a^2}=\frac{\Gamma(\frac{b}{2})}{48\Gamma(1+\frac{b}{2})}(6\gamma^2+\pi^2+12\gamma\psi_0(1+\frac{b}{2})+6\psi_0^2(1+\frac{b}{2})-6\psi_1(1+\frac{b}{2}))) $$ and hence \begin{eqnarray} \frac{\partial^3 J(0,b)}{\partial a^2\partial b}&=&\frac{\Gamma(\frac{b}{2})}{96\Gamma(1+\frac{b}{2})}[-6\psi_0^3(1+\frac{b}{2})+6\psi_0^2(1+\frac{b}{2})(-2\gamma+\psi_0(1+\frac{b}{2}))\\ &&+\psi_0(\frac{b}{2})(6\gamma^2+\pi^2-6\psi_1(1+\frac{b}{2}))+12\gamma\psi_1(1+\frac{b}{2})+\gamma\psi_0(1+\frac{b}{2})(-6\gamma^2-\pi^2\\ &&+12\gamma\psi_0(\frac{b}{2})+18\gamma\psi_1(1+\frac{b}{2}))-6\gamma\psi_2(1+\frac{b}{2})). \end{eqnarray} Noting, for $z\in(0,1)$, $$ \Gamma(1)=1, \Gamma(1-z)\Gamma(z)=\frac{\pi}{\sin(\pi z)} $$ we have $$ \Gamma(\frac{b}{2})\approx\frac{\pi}{\sin(\frac{b\pi}{2})}, \psi_0(1+\frac{b}{2})=-\gamma+\frac{\pi^2b}{12}+O(b^2).$$ From this, we have \begin{eqnarray} \psi_0(\frac{b}{2})&=&-\frac{2}{b}-\gamma+\frac{\pi^2b}{12}+O(b^2)\\ \psi_0(1+\frac{b}{2})&=&-\gamma+\frac{\pi^2b}{12}+O(b^2)\\ \psi_1(1+\frac{b}{2})&=&\frac{\pi^2}{6}+\frac{b}{2}\psi_2(1)+\frac{\pi^4b^2}{120}+O(b^3)\\ \psi_2(1+\frac{b}{2})&=&\psi_2(1)+\frac{\pi^4b}{30}+O(b^2), \end{eqnarray} and hence \begin{eqnarray} \frac{\partial^3 J(0,b)}{\partial a^2\partial b}&\approx&\frac{b\pi^3}{11520\sin(\frac{b\pi}{2})}(-2\pi^2+b^2\pi^4+60b\psi_2(1)). \end{eqnarray} So $$ \frac{\partial^3 J(0,0)}{\partial a^2\partial b}=\lim_{b\to0}\frac{\partial^3 J(0,b)}{\partial a^2\partial b}=\lim_{b\to0}\frac{b\pi^3}{11520\sin(\frac{b\pi}{2})}(-2\pi^2+b^2\pi^4+60b\psi_2(1))=-\frac{\pi^4}{2880}.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.